The Warship Division’s Strategy Development of PT. PAL to Strengthen the National Defense Industry - Hudayah Ramadhan; Achmad Faisol; Hari Subagyo (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2023)
The strength of a country can be interpreted to align with its independence and capability of a defense industry so that its defense industry can be strong enough to maintain the existence of a country. The capability of the defense industry is also influenced by the direction of government policy, as is the vision and mission of the Ministry of Defense which is committed to improving the defense industry, one of which is PT. PAL, which is engaged in the maritime sector in shipbuilding and maintenance. To realize the government's vision and mission, PT. PAL felt the need to provide more exploration in developing its warship division. In developing the warship division, a special strategy is needed to achieve the PT. PAL desired target. This study aims to determine the strategy for the development of the warship division at PT. PAL. This study uses a descriptive analysis method with a qualitative approach. The study was conducted in the Warship Division of PT. PAL which is located at Ujung Street in Surabaya. Sources of data in this study are informants and documents. The data collection technique is triangulation. The results showed that the strategy used was a differentiation strategy and a focus strategy with breakthrough steps including implementation of front-end back-end mechanisms in business development, project financing to optimize production facilities, increasing productivity through the implementation of the Full Block Outfitting System (FSOB), optimization of production equipment, the productivity of measurement center, the productivity of welding center, quality policies and other policies that lead to the implementation of Good Corporate Governance practices at PT. PAL.